Taxonomy and phylogeny of Albian-Maastrichtian planispiral planktonic foraminifera traditionally assigned to Globigerinelloides - Huber, Brian T.; Petrizzo, Maria Rose; Falzoni, Francesca (Micropaleontology, 2022)
We propose a considerably revised taxonomy and phylogeny for Albian-Maastrichtian planispiral planktonic foraminiferal species that have traditionally been included in Globigerinelloides. The revised taxonomy is necessary because of a similar to 6 m.y. gap between the extinction of planispiral species during the late Aptian and the next younger occurrence of planispiral species in the middle Albian. Our stratophenetic taxonomic groupings utilize ontogenetic morphometric data, shell wall ultrastructure, and general morphologic features observed from Scanning Electron Microscope and X-radiograph images of primary type specimens and globally distributed hypotype specimens.The planispiral lineage Laeviella n. gen., whose type species is La. bentonensis (Morrow), first appeared in the middle Albian and is postulated to have evolved from the evolutionary series Ticinella primula Luterbacher-Laviella primuloides n. sp. Laeviella is characterized as having a smooth to finely pustulose wall texture and a moderate chamber size increase rate. Two additional species, La. tururensis (Bronnimann) and La. bollii (Pessagno), are included in Laeviella with the youngest species of the genus, La. bollii, becoming extinct during the late Campanian.Planohedbergella, with Plh. aspera (Ehrenberg) as its type species, is revised to include 10 species that show a wide variation in chamber arrangement, wall microstructure and test morphology, but all have a moderately to coarsely pustulose wall texture on some or most final whorl chambers. Its stratigraphic range is from the late Albian-Cretaceous/Paleogene boundary. The oldest species is Plh. ultramicra (Subbotina), which evolved from Planomalina pulchella Todd and Low during the late Albian. Planohedbergella circularis n. sp. is described as a new late Campanian-Maastrichtian species representing forms with evolute coiling, a large number of final whorl chambers, and a slow chamber size increase rate.Polycamerella n. gen. is described as a monospecific genus, with Po. tardata n. sp. as ...